Enteral Ca-Intake May Be Low and Affects Serum-PTH-Levels in Pre-school Children With Chronic Kidney Disease - Schmitz, Lilith; Hoermann, Pamela; Trutnau, Birgit; Jankauskiene, Augustina; Zaloszyc, Ariane; Edefonti, Alberto Carlo; Schmitt, Claus Peter; Klaus, Guenter (Frontiers in Pediatrics, 2021)
Treatment of chronic kidney disease mineral bone disorder is challenging in pediatric CKD patients due to high amount of calcium needed for normal bone mineralization. To control serum phosphate, reduced intake of milk products might affect Ca-homeostasis in the growing child. Therefore enteral calcium-intake (Ca-I) was calculated. Patients: Pediatric CKD-Patients aged 0-6 years Design: Retrospective analysis of Ca-I from dietary data collections. A Ca-I below 60% or above 120% of the D-A-CH or above the KDOQI reference were considered as severe Ca deficiency or Ca overload. Results: 41 children, median age 1.1 (0-5.8) years, body weight 7.3 (2.4–19.9) kg, length 68 (48-105) cm at time of first dietary data collection. Renal function was classified as CKD stage III in 20, IV in 28, V in 44, VD in 142, and after renal transplantation in 2 dietary data collections. At the first dietary data collection 5 children were in in CKD stage III, 10 in IV, 9 in V, and 16 were on dialysis and 1 after renal transplantation. Only one child progressed to a higher CKD stage. 236 dietary data collections were analysed. 65 follow-up collections were available from 33 children, time between the first and the second collection was 26 (1-372) days. Median caloric intake was 120 (47-217) % of D-A-CH RDI. In 148 (62.7%) of the dietary data collections, enteral Ca-I was below target (100% of the D-A-CH RDI). Analysing the first and 2nd dietary data collection, severe Ca-deficiency was found in 11 (26%) and 4 (12%) children. Only 11 children took Ca-containing phosphate binders. When the Ca content of the phosphate binders was included in the analysis, 3 and 4 children were Ca overloaded according to D-A-CH and KDOQI RDI. These number decreased from collection 1 to collection 2 (4 vs 0 patients). Absolute dietary Ca-I and Ca-I normalized to body weight correlated negatively with PTH (r=-0.196, p<0.005 and r=-0.13, p<0.05). Conclusion: Enteral Ca-I should repeatedly be monitored in CKD children, because a significant number may otherwise be under- or overexposed to enteral calcium load. Our findings suggest a significant impact on bone health in pediatric CKD.